Shaping Concepts of Technology
V, 201 p.
Keywords: As our modem society is so obviously influenced by technology, there is a growing awareness of its importance for education. The interest for including technology as a part of general education curricula is increasing. In many countries technology is an element in the curriculum either as a topic, a project, part of a Science-Technology-Society (STS) programme, part of science education, or as a separate subject. In order to clarify what technology is, there is a need for international discussions in which philosophers, engineers, scientists and educational ists are involved. One of the few conferences with such a broad representation was the second Jerusalem International Science and Technology Education Conference (JISTEC) that was held in Jerusalem, January 8-11, 1996, a conference that can truly be seen as a milestone in the international history of technology education. More than 1,000 technology educators from more than 80 countries of the world and ministers of education from 28 coun tries came together to discuss current issues in technology education during JlSTEC. To cite from Dr. Michael Dyrenfurth's personal overview of the conference in the Journal of Industrial Teacher Education (vol. 33, no. 2, Winter 1996, pp. 83-85): 'Simply put, this conference represented the most stellar international collection of technology education advocates the world has ever seen in one place'. Or in the words of Dr.